Optimizing the Potential of Solar Energy PT PJB UP Muara Karang Rooftop Area Using HelioScope - Samsurizal Samsurizal; Rio Afrianda; Andi Makkulau (Faculty of Engineering, Universitas Tanjungpura, 2022)
Year after year, there has been a rise in use of electrical power. The industrial, home, commercial, and public sectors accounted for 234,617.88 GWh of PLN's electrical energy sales in 2018. Meanwhile, the household, industrial, commercial, social sector, government office buildings, and public street lighting consumed 2,857.06 GWh of electrical energy in DKI Jakarta. The majority of the energy resources required by interconnected networks are fossil (coal). As a result, a future alternative to fossil fuels is required. Optimizing solar energy that may be employed in urban settings is one of the uses of renewable energy. The building sector consumes up to 40% of the total annual energy. By installing a renewable energy system on the roof of PT PJB Muara Karang power plant unit. The solar power plant energy potential on the roof of PT PJB UP Muara Karang administration building was simulated with HelioScope and using Quantitative Descriptive Method to maximize the rooftop area by installing 143 solar panel modules. which is capable of supplying 75.11 percent of the energy needs at PT. PJB UP Muara Karang.